ANTICANCER ACTIVITIES OF SECONDARY METABOLITES PRODUCED BY TAXUS ENDOPHYTIC FUNGUS PHOMOPSIS CHIMONANTHI - A. Desak Gede Sri; J. p. Raymond; Harmastmi Harmastini; L.B. S. Kardono,; M. Hanafi; E. Meiyanto (Research Center for Chemistry - LIPI, 2011)
Secondary metabolite by the Taxus endophytic fungus strain Tse3 culture obtained from the West Java Forest has been produced. Production of secondary metabolite had done by aerobic fermentation for 7 days, 3(fC, 120 rpm in PDB (potato dextrose broth) media. The broth of fermentation was extracted by ethyl acetate. Various concentrations of the ethyl acetate extract in (0- 800) mcg/mL were prepared and test against T47D cancer cell line. Cytotoxic test has be done by MTTmethod. ICso value of ethyl acetate extract was 3 mcg/mL. The result of fungus identification by morphology and molecular 18S rRNA was Phomopsis chimonanthi.Key words: Phomopsis chimonanthi, fermentation, isolation, cytotoxicity, identification, taxus